GREEN SCHOOL: Creating an Environmental Friendly and Sustainable School at Muhammadiyah PK Sambi Elementary School - Priyana, Yuli; Hidayat, Iqbal Agung; Fatkhiyah, Maulida; Sari, Dewi Novita (Journal of Community Services and Engagement: Voice of Community (VOC), 2024)
Green School is a concept that promotes the use of environmental friendly and sustainable practices in daily school activities. This includes efficient energy use, waste reduction, responsible water management, and comprehensive environmental education. The goal of this initiative is to raise awareness and implement eco-friendly school practices at Muhammadiyah PK Sambi Elementary School, Boyolali.   The implementation methods involve brief lectures, discussions, and hands-on activities, such as planting greenery in the schoolyard. The research results indicate an increase in environmental awareness and the implementation of eco-friendly practices in the school. Key findings include reduced energy consumption, more efficient waste management, and heightened environmental awareness among students and school staff. In conclusion, the application of the Green School concept is effective in creating an environmental friendly and sustainable school and can serve as a model for other educational institutions. This effort can contribute positively to addressing global environmental challenges and preparing future generations who care about the environment.